Community Empowerment through Clean and Healthy Lifestyles to Improve Health Degrees in Indonesian Community - Andiko Nugraha Kusuma (Jurnal Mantik, 2021)
Health is one of the focuses of attention in every country, because having a healthy community can certainly create a productive society, and by always getting used to a clean and healthy lifestyle the community can support government programs to form Superior Human Resources (HR) and highly educated. This study uses a qualitative method with the aim that there is greater spontaneity and better adaptation of the interaction between researchers and research sources in obtaining answers to research questions. There are various data collection methods in this qualitative research, namely observation, textual analysis and interviews (individual or group). So the results of this study explain that the formation of clean and healthy living behavior from an early age is very important to implement, so that gradually this activity will become a good habit of life and become an initial capital in the process of human growth and development in the future. The application of PHBS indicators as a behavior of people's lives is very important, but other indicators are no less important in the formation of healthy living behavior so as to create a high degree of public health. One part of PHBS is washing hands with soap before and after doing an activity. Good hand washing is to follow the 7 steps of cleaning hands according to the correct procedure to kill germs that cause disease. On the other hand, outreach to the community is a strategic effort to empower every member of the household to always apply a clean and healthy lifestyle, so that the community is able to help themselves. In addition, it is also necessary to instill in the community character values, so that clean and healthy living behaviors really grow and are well embedded in people's lives.